1963
DOI: 10.1071/ph630570
|View full text |Cite
|
Sign up to set email alerts
|

A Low Resolution Hydrogen-line Survey of the Magellanic System. II. Interpretation of Results

Abstract: SummaryA low resolution (2?2) survey of the neutral hydrogen in the Magellanic Clouds has produced two important additions to our knowledge of the system. (1) A bridge of gas between the Small and Large Cloud has been mapped. (2) The Small Cloud profiles show double peaks over a wide area, suggesting the possibility of two substantially separate masses of gas.The observations are discussed in terms of the distribution of integrated brightness and the median velocity of the H·line profiles. Contours of integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
1

Year Published

1963
1963
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 9 publications
3
82
0
1
Order By: Relevance
“…A continuous H i gas structure between the LMC and the SMC, known as the Magellanic Bridge (MB), was first reported by Hindman et al (1963), and it is found to be at a distance of ∼50-60 kpc (e.g., Harries et al 2003). There is substantial evidence for a young stellar population in the MB, with stars as young as ∼20 Myr (Irwin et al 1985(Irwin et al , 1990Grondin et al 1992;Hambly et al 1994;Demers & Battinelli 1998) and with molecular clouds detected (Lehner 2002;Muller et al 2003;Mizuno et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A continuous H i gas structure between the LMC and the SMC, known as the Magellanic Bridge (MB), was first reported by Hindman et al (1963), and it is found to be at a distance of ∼50-60 kpc (e.g., Harries et al 2003). There is substantial evidence for a young stellar population in the MB, with stars as young as ∼20 Myr (Irwin et al 1985(Irwin et al , 1990Grondin et al 1992;Hambly et al 1994;Demers & Battinelli 1998) and with molecular clouds detected (Lehner 2002;Muller et al 2003;Mizuno et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Stanimirovic et al 2000;Kemper et al 2010;Bolatto et al 2011;Matsuura, Woods & Owen 2013). Indeed various gaseous features were created by the interactions of the MCs with each other and with the Milky Way (MW) such as the Magellanic Bridge (MB; Hindman, Kerr & McGee 1963), a common envelope of H I spanning ∼13 kpc in which both the Large Magellanic Cloud (LMC) and the Small Magellanic Cloud (SMC) are embedded; the Magellanic Stream, a pure gaseous stream trailing the MCs as they orbit the MW (Mathewson, Cleary & Murray 1974;Nidever et al 2010) connecting both of the MCs with the MW, and the Leading Arm, a mass of high-velocity clouds leading the MCs (Putman 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The profile at each of these points is plotted A striking feature of Figure 13 is the regular splitting into two peaks of the H-line profiles of the Small Magellanic Cloud. A discussion of the phenomenon is given in paper II (Hindman, Kerr, and McGee 1963). …”
Section: (D) Profilesmentioning
confidence: 99%